Mitochondrial dynamics altered by oxidative stress in cancer. (2nd October 2016) - Kim, Boyun; Song, Yong Sang
Abstract: Mitochondria as crucial organelles regulate cellular energy generation, calcium and redox homeostasis, and apoptosis. To perform the cellular functions effectively, mitochondria continuously change their structure and morphology through protein machineries controlling fission and fusion process (mitochondrial dynamics). Traditionally, many researches had focused on the interaction of mitochondrial dynamics and apoptosis. However, recent studies are reporting the alteration of mitochondrial dynamics in human diseases including many types of cancers. Considering that cancers maintain a high level of reactive oxygen species (ROS), mitochondrial dynamics can be influenced by oxidative stress. In this review, we will discuss the alteration of mitochondrial dynamics by ROS and its effect on metastasis and chemoresistance in cancers.